1995
DOI: 10.1002/aja.1002030108
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of vitronectin mRNA during murine development

Abstract: Vitronectin (Vn) is not only a major adhesive glycoprotein in plasma but also regulates cell-mediated proteolytic enzyme cascades, including the complement, coagulation, and fibrinolytic systems. This broad functional activity suggests that Vn may also play a critical role in development. To begin to investigate this possibility, we studied Vn gene expression during murine embryogenesis. In situ hybridization analysis of embryonic tissues revealed Vn mRNA primarily in the liver and the central nervous system (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
1

Year Published

1995
1995
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 19 publications
1
34
1
Order By: Relevance
“…VN is widely distributed in the ECM of many tissues in adult humans (1,2) and during embryogenesis in the mouse (30). Despite extensive prior studies suggesting a major role for VN in the developing embryo, particularly during central nervous system and heart organogenesis (7,8,30), we failed to detect any disturbance of normal growth or development in mice engineered to be completely deficient in VN. These data suggest some degree of overlap or compensation by other ECM proteins in support of these critical developmental functions.…”
Section: Targeted Disruption Of the Vn Gene In Es Cells Es Cellscontrasting
confidence: 59%
“…VN is widely distributed in the ECM of many tissues in adult humans (1,2) and during embryogenesis in the mouse (30). Despite extensive prior studies suggesting a major role for VN in the developing embryo, particularly during central nervous system and heart organogenesis (7,8,30), we failed to detect any disturbance of normal growth or development in mice engineered to be completely deficient in VN. These data suggest some degree of overlap or compensation by other ECM proteins in support of these critical developmental functions.…”
Section: Targeted Disruption Of the Vn Gene In Es Cells Es Cellscontrasting
confidence: 59%
“…Up-regulation of vitronectin expression is also observed in notochord and floor plate during mouse and chick neurogenesis (Seiffert et al, 1995;Martinez-Morales et al, 1997;Pons and Marti, 2000). Our previous study showed that Foxa regulates the constitutive expression of vitronectin through site B (Shimizu et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we showed that Foxa is involved in the up-regulation of vitronectin expression during the retinoic acid-induced differentiation. Transcription factors Foxa1 and Foxa2, which are members of the Foxa family (Lai et al, 1990;Kaestner, 2000;Kaestner et al, 2000), are expressed in liver, notochord and floor plate (Monaghan et al, 1993;Sasaki and Hogan, 1993;Seiffert et al, 1995). In point of detail, the internal granular layer of the cerebellum and mouse embryonic carcinoma P19 cells express Foxa1 and/or Foxa2 during the neuronal differentiation (Jacob et al, 1997;Dahmane and Ruiz-i-Altaba, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vitronectin deposition into the matrix is tightly regulated, occurring at specific times during development and disease progression. In the adult animal, vitronectin synthesis occurs primarily in the liver (71,72,78), however, induction of vitronectin synthesis by tissue cells and its increased deposition into surrounding 86 C. E. WILKINS-PORT ET AL. tissues has been observed in association with tumor progression (6,7,26,27,80), atherosclerosis (17,83), rheumatoid arthritis (79), macular degeneration (29,57), and differentiation of neuroectodermal and mesenchymal structures (16,40,48,71). Vitronectin has a relatively short half life in the matrix as it is actively removed by integrin receptor mediated endocytosis and subsequently degraded by lysosomal enzymes (49,59).…”
Section: Introductionmentioning
confidence: 99%